What is evolutionary computation?. - Fogel, D.B (IEEE spectrum)
Taking a page from Darwin's 'On the origin of the species', computer scientists have found ways to evolve solutions to complex problems. Harnessing the evolutionary process within a computer provides a means for addressing complex engineering problems-ones involving chaotic disturbances, randomness, and complex nonlinear dynamics-that traditional algorithms have been unable to conquer. Indeed, the field of evolutionary computation is one of the fastest growing areas of computer science and engineering for just this reason; it is addressing many problems that were previously beyond reach, such as rapid design of medicines, flexible solutions to supply-chain management problems, and rapid analysis of battlefield tactics for defense. Potentially, the field may fulfil the dream of artificial intelligence: a computer that can learn on its own and become an expert in any chosen area